PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN PELANGGAN DOMPET ELEKTRONIK OVO (Studi Kasus Pengguna OVO di Kota Tangerang Selatan) - Esya Andini Putri, (2022)
The research objective is to prove that there is an effect of service quality on customer satisfaction and trust on customer satisfaction. This research is a quantitative research with primary data sources. The object of this research is an OVO electronic wallet users who is domiciled in South Tangerang City. The sample used was 100 respondents and dominated by teenagers using purposive sampling technique as a data collection technique. The data analysis technique used is descriptive and inferential data analysis techniques. Based on the results of data processing through t-statistics on the Smart PLS software, it can be shown that (1) service quality has a significant effect on customer satisfaction. (2) trust has a significant effect on customer satisfaction